2010
DOI: 10.1130/b30040.1
|View full text |Cite
|
Sign up to set email alerts
|

The mid-Ordovician Osmussaar breccia in Estonia linked to the disruption of the L-chondrite parent body in the asteroid belt

Abstract: The Middle Ordovician (466 Ma) Osmussaar breccia, situated along the northwestern coast of Estonia, is rich in angular chromite grains of extraterrestrial origin (>13 grains kg -1 ) and shocked quartz. The angularity of the chromite grains implies that they have not been transported or reworked to any large extent, connoting that the brecciation is the result of a contemporary impactor, either as a direct consequence of the impact or as a result of an earthquake triggered by the impact, and thus is not, as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…A gradual thinning away from Osmussaar Island, together with the west-east oriented elliptical dispersion (Fig. 1B), suggest that the generating event epicentrum is located not too far from the island (Suuroja et al 2003;Alwmark et al 2010).…”
Section: Introductionmentioning
confidence: 92%
“…A gradual thinning away from Osmussaar Island, together with the west-east oriented elliptical dispersion (Fig. 1B), suggest that the generating event epicentrum is located not too far from the island (Suuroja et al 2003;Alwmark et al 2010).…”
Section: Introductionmentioning
confidence: 92%
“…platinum group element enrichment, high chondritic ratios, Re-Os and/or Cr isotopic evidence) (French and Koeberl, 2010). Indeed, Suuroja et al (2003) reported about the finding of shock-metamorphic features (PDF) in quartz grains, and study by Alwmark et al (2010) documented extraterrestrial chromite enrichment, both from the infill of large sedimentary dykes on Osmussaar Island. This enabled them to present a possible relationship of the large sedimentary dykes to a yet unknown meteorite impact event (Suuroja et al, 2003;Alwmark et al, 2010).…”
Section: Triggering Mechanismmentioning
confidence: 91%
“…Indeed, Suuroja et al (2003) reported about the finding of shock-metamorphic features (PDF) in quartz grains, and study by Alwmark et al (2010) documented extraterrestrial chromite enrichment, both from the infill of large sedimentary dykes on Osmussaar Island. This enabled them to present a possible relationship of the large sedimentary dykes to a yet unknown meteorite impact event (Suuroja et al, 2003;Alwmark et al, 2010). Detailed conodont dating of the undeformed bed at the top of the Pakri Formation in Osmussaar Island dated the deformation event to the early or middle part of the early Darriwilian Kunda Regional Stage (Mellgren et al, 2012) (Fig.…”
Section: Triggering Mechanismmentioning
confidence: 96%
See 1 more Smart Citation
“…The Middle Ordovician is composed of several sedimentary units described as local stages: Volkov, Kunda, Aseri, Lasnamägi, and Uhaku in ascending order Plado et al, 2010;Smethurst et al, 1998). In northwestern Estonia, the Kunda stage records a meteoritic shower event on the Island of Osmussaar (Alwmark et al, 2010).…”
Section: Middle Ordovician Stages Studiedmentioning
confidence: 99%